2021
DOI: 10.3390/e23111483
|View full text |Cite
|
Sign up to set email alerts
|

Energy, Exergy, Exergoeconomic and Exergoenvironmental Impact Analyses and Optimization of Various Geothermal Power Cycle Configurations

Abstract: Energy, exergy, and exergoeconomic evaluations of various geothermal configurations are reported. The main operational and economic parameters of the cycles are evaluated and compared. Multi-objective optimization of the cycles is conducted using the artificial bee colony algorithm. A sensitivity assessment is carried out on the effect of production well temperature variation on system performance from energy and economic perspectives. The results show that the flash-binary cycle has the highest thermal and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Exergoeconomics is a powerful and influential knowledge driven by a combination of economic and exergy concepts; it helps researchers better understand systems from an exergy and economic point of view. It makes possible the economic design of power systems that cannot be obtained by standard economic models [ 13 , 22 ]. In exergoeconomic analysis, a cost value is associated with each exergy flow within a system, since exergy is considered the only rational basis for assigning the cost of a thermal system [ 17 , 46 ].…”
Section: Thermodynamic Economic and Environmental Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exergoeconomics is a powerful and influential knowledge driven by a combination of economic and exergy concepts; it helps researchers better understand systems from an exergy and economic point of view. It makes possible the economic design of power systems that cannot be obtained by standard economic models [ 13 , 22 ]. In exergoeconomic analysis, a cost value is associated with each exergy flow within a system, since exergy is considered the only rational basis for assigning the cost of a thermal system [ 17 , 46 ].…”
Section: Thermodynamic Economic and Environmental Modelsmentioning
confidence: 99%
“…In addition to exergetic and exergoeconomic methods, exergoenvironmental analysis, which is a combination of exergetic analysis and life cycle assessment (LCA) concepts, is a recent method for evaluating the environmental impacts of energy conversion systems, such as geothermal power plants with waste heat recovery [ 18 ]. Several authors have investigated this type of systems from this perspective [ 19 , 20 , 21 , 22 , 23 , 24 ]. Table 1 shows previous works focused on evaluations of a low temperature ORC cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings highlighted the efficiencies of the first and second laws of thermodynamics for both configurations, offering insights into the operational variables that affect exergy destruction in geothermal plants. Shamoushaki, et al 22 reported on energy, exergy, and exergoeconomic evaluations of various geothermal configurations, using the artificial bee colony algorithm for optimization. They found the flash‐binary cycle to have the highest thermal and exergy efficiencies, demonstrating the influence of production well temperature on system performance.…”
Section: Introductionmentioning
confidence: 99%
“…The exergoeconomic analysis enabled the determination of the monetary cost of the output power and the capital investment amortization rate of the key apparatuses. Shamoushaki M. et al [ 15 ] conducted a comprehensive analysis and optimization of different configurations of power cycles. The method of analysis combined the energetic and exergoeconomic balances.…”
Section: Introductionmentioning
confidence: 99%